The Influence Of Asset Management Towards Optimization Of State Assets In Working Units In The Denpasar High Court Region - Ni Luh Putu Sriastiti; Ni Luh Anik Puspa Ningsih; Putu Ngurah Suyatna Yasa (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
This study aims to analyze the effect of asset management which includes planning needs, inventory, identification, legal audit, asset valuation, utilization and monitoring of asset optimization in employees in charge of assets in the Denpasar High Court Regional Work Unit. The data used in this study are primary data obtained through questionnaires. The population in this study were all employees in the field of assets in the Denpasar High Court Regional Work Unit, amounting to 73 people. Determination of the sample using the census technique in which all populations are sampled. Data analysis technique uses Partial Least Square with the help of PLS software program. Based on the results of hypothesis testing it can be stated that the Requirement Planning significantly positive effect on asset optimization. Inventory does not have a significant positive effect on asset optimization. The identification of positive effect is not significant on asset optimization. Legal audit does not have a significant positive effect on asset optimization. Asset valuation has a positive and significant effect on asset optimization. Utilization has a positive and not significant effect on asset optimization. And monitoring has a positive and not significant effect on asset optimization.